Свидание в полночь - Копейко Вера Васильевна (Роман для девочек. До 13 и старше, 2003)
Экземпляры: ф.21 (2003) / Инвентарный номер: 47196 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: К 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44